Synthesis of silver nanoparticles from Padina australis seawedd extract as bioreductor - A. Nur Ainun (International Journal of Applied Biology, 2022)
The synthesis of silver nanoparticles was carried out using silver nitrate solution as a precursor and Padina australis seaweed as a bioreductor. This study aims to obtain silver nanoparticles through the green synthesis method using Padina australis seaweed extract. The process of forming silver nanoparticles was carried out by adding Padina australis seaweed extract to 1mM AgNO3 solution. The nanoparticles were characterized using a UV-Vis spectrophotometer instrument. The results of the UV-Vis spectrum analysis showed that the best nanoparticle synthesis was shown in the 0.5% concentration extract with a duration of 30 minutes with a synthesis temperature of 70°C, with an absorbance peak at a wavelength of 445.00 nm. Based on visual observation, the extract turned reddish brown.